Disseminated Histoplasmosis with Underlying Sarcoidosis-Rheumatoid Arthritis Overlap Syndrome: An Example of Diagnostic Test Threshold of Detection Affecting Test Results and Patient Care - Daniel Pankratz; Jordan Tichenor; Fernando Merino; Nathan C. Bahr (Case Reports in Infectious Diseases)
Histoplasmosis is common in many parts of the world but with areas of hyperendemicity. Disseminated histoplasmosis is the deadliest form of histoplasmosis and is most common among immunocompromised patients. Timely diagnosis is crucial to improve outcomes. We describe a patient on azathioprine and rituximab with disseminated histoplasmosis in which diagnosis was delayed in part because of negative early Histoplasma antigen testing, which was positive later in the course. This case serves as an example of the concept of “threshold of detection” in which a certain concentration of a microbe must be present for it to be detected by a diagnostic test that focuses on detection of a microbe or its components. This concept applies to many tests used to diagnose infectious diseases.